Neuraxial block versus general anaesthesia for cesarean section: post-operative pain scores and analgesic requirements - (:unkn) unknown (PAKISTAN MEDICAL ASSOC, 2012)
Objective: To evaluate the suitability of spinal and general anaesthesia for cesarean section. Methods: The prospective, double-blinded study, done between March and December 2009, at Central Education and Research Hospital, Erzurum, Turkey, involved 60 patients undergoing elective cesarean surgery. They were grouped according to the kind of anaesthesia, with each group having 30 patients each. Postoperative pain scores, opioid requirement, side effects and patient satisfaction were compared through statistical analysis using SPSS version 10. Results: Patient demographics were similar in both groups. Patients in the general anaesthesia group consumed 638.4 +/- 179.10 mu g fentanyl, while patients in the spinal anaesthesia group consumed 356.3 +/- 87.1 mu g. The number of patients requiring opioid via Patient Controlled Analgesia in the first 24 hours was significantly higher in the general anaesthesia group. Patient satisfaction was significantly higher in the spinal anaesthesia group. Conclusion: Type of anaesthesia for elective cesarean section is important to provide sufficient post-operative analgesia and patient satisfaction.
Keywords: Analgesia; Post-operative pain; Cesarean delivery; Fentanyl; FENTANYL; OUTCOMES